ANALISIS VEGETASI TUMBUHAN BAWAH DI HUTAN RAWA GAMBUT KABUPATEN BANJAR - Kardiannor Kardiannor; Dina Naemah; Normela Rachmawati (Universitas Lambung Mangkurat, 2022)
Undergrowth has an important function for soil fertility because it is a source of litter. The undergrowth plants on peatlands that have various types can be used by the surrounding community for both medicinal plants and food sources. Peatlands have an important ecological function as a life support ecosystem. The composition and structure of plants can be used to see the dominance of a plant species in the area. This study aims to identify understorey species, analyze the level of control of understorey species found in the Peat Swamp Forest, Gambut District, Banjar Regency. This peat swamp area has a characteristic that it is always flooded and acidic, therefore only certain plants can live. Collecting data from the field using the checkered path method. Data analysis used the calculation of Significant Value (INP), Species Diversity Index the Shanon-Wiener (H') and Summed Dominance Ratio (SDR). The types of understorey found in this study were 25 species of understorey from 19 families. The three understorey species that have the highest importance are Chrysopogon aciculatus: 48.83% (Poaceae: Fam), Ludwigia adscendens: 31.40% (Poaceae: Fam), Lepironia articulate: 24.01% (Cyperaceae: Fam), Rhodomyrtus tomentosa: 19.21% (Myrtaceae: Fam), and Cyperus esculentus: 19.17% (Cyperaceae: Fam)Tumbuhan bawah memiliki fungsi penting untuk kesuburan tanah karena merupakan salah satu sumber serasah. Tumbuhan bawah di lahan gambut yang memiliki bervariasi dapat dimanfaatkan oleh masyarakat sekitar baik untuk tumbuhan obat maupun sumber pangan. Lahan gambut memiliki fungsi ekologis penting sebagai ekosistem penyangga kehidupan. Komposisi dan struktur tumbuhan dapat digunakan untuk melihat dominansi suatu jenis tumbuhan di wilayah tersebut. Penelitian ini bertujuan untuk mengidentifikasi jenis-jenis tumbuhan bawah, menganalisa tingkat penguasaan jenis tumbuhan bawah yang terdapat di Hutan Rawa Gambut Kecamatan Gambut Kabupaten Banjar. Wilayah rawa gambut ini memiliki ciri khas selalu tergenang dan bersifat masam oleh karena itu hanya tumbuhan tertentu saja yang dapat hidup. Pengambilan data dari lapangan menggunakan metode jalur berpetak. Analisis data menggunakan perhitungan Nilai Penting (INP), Indeks Keanekaragaman jenis Shanon-Wiener (H’), dan Summed Dominance Ratio (SDR) dan. Jenis tumbuhan bawah yang ditemukan pada penelitian ini adalah 25 jenis tumbuhan bawah dari 19 famili. Tiga jenis tumbuhan bawah yang memiliki nilai penting tertinggi ialah jenis Chrysopogon aciculatus: 48,83% (Poaceae: Fam), jenis Ludwigia adscendens: 31,40% (Poaceae: Fam), jenis Lepironia articulate: 24,01% (Cyperaceae: Fam), Rhodomyrtus tomentosa: 19,21% (Myrtaceae: Fam), dan jenis Cyperus esculentus: 19,17% (Cyperaceae: Fam).